PERAN MEDIASI MANAJEMEN LABA PADA PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN - Cindy Berliana Menti; Widiastuty, Erna (Faculty of Economics and Business University of Mataram, 2024)
This research aims to examine the role of earnings management in mediating the effect of CSR disclosure on financial performance. This type of research is quantitative and carried out on public companies listed on the European Stock Exchange for 2013-2022. Sampling using the purposive sampling method obtained 1,690 company-year observations. ESG scores measure CSR disclosure. Financial performance is measured using ROA, ROE, and Tobin's Q, while earnings management uses discretionary accruals. The secondary data source comes from Eikon's Revinitif Datastream. The results show that the effect of CSR disclosure on company financial performance, mediated by earnings management, is mixed. When ROE measures financial performance, it shows that the hypothesis is not supported. Meanwhile, the hypothesis is supported when ROA and Tobin's Q measure financial performance. The results of this research imply that CSR disclosure encourages information transparency, which signals the company's financial performance.